Desenvolvimento de um ensaio mecânico não convencional para a análise da relaxação de tensões do politetrafluoretileno - Melo, Caiuã Caldeira de (2016)
The mechanical behavior of materials usually depends on room temperature and loading rate. The identification of the time-dependent mechanical behavior is a great difficulty for the industry in the application of new materials such as polymers, mainly for long-term behavior. In this context, several experimental apparatus for measuring mechanical properties of long-term behavior have been developed. Generally, these devices are expensive and its use is unique to a specimen tested at one time. This study is a development of a new technique and methods for the characterization of time-dependent mechanical behavior in longterm tests. The hole-shaft coupling test (HSCT) was developed to the low cost of implementation and, especially, not a continued occupation of a testing machine for long periods, allowing the performance of more than one test at the same time. The HSCT results revealed the stress relaxation effects on polytetrafluoroethylene over several days. An optimization with finite element (FE) simulations assistance was carried out to characterize the viscoelastic material and obtain Maxwell generalized model parameters, an analytical formulation was also performed. Additionally, the strains were measured during recovery of the material by digital image correlation (DIC). The HSCT proved to be feasible for measuring the long-term stress relaxation, demonstrating the advantages mentioned above. The FE simulations reproduced qualitatively the mechanical behavior of the material, as well as the analytical model developed. Measurement of strain recovery after HSCT via DIC is presented a way to enrich the characterization of the material.